Working Capital Turnover Terhadap Rentabilitas Bank Perkreditan Rakyat - Dewi, Kemala; Arjana, Ida Bagus Made; Juniawan, Ida Bagus Heri (IAHN Gde Pudja Mataram, 2022)
The purpose of measuring economic profitability is to obtain an overview of the effectiveness and efficiency of BPRs in maximizing the management of working capital to earn profits. The use of effective and efficient working capital does not necessarily indicate the ability of the BPR to earn a profit. In obtaining BPR profits can be measured using the ratio of cash turnover and receivables turnover. Economic profitability is a measure of BPR in generating profits. Economic profitability can be achieved if the working capital turnover is fast. The method used is narrative analysis through literature review